Desenvolvimento municipal no Brasil: uma análise a partir da concepção teórica de Karl Polanyi - Santos, Nayara Silva dos (Universidade Federal do Tocantins, 2016)
For long, the idea of development had been linked to the expansion of the capitalist ways of production as well as their consequences as to the technical and riches accumulation progress. The contemporaneous debate, however, has rescued Karl Polanyi's principles and themes. This has been done both during and after the second world war, what has evidenced the update and how important the rediscovery of his thought is. This study aims to analyze the city development in Brazil from Karl Polanyi's theoretical conception. To do so, a rereading on the social coordination principles which were evidenced by Polanyi (1947; 2012a; 2012b) has been taken so that these principles become represented by four dimensions: State, market, sympathy and subsistence which form the multidimensional approach. Through the multidimensional approach, the polanyian city development index (PCDI) has been structured. This one has two outstanding aims: a) allowing the visualization on the brazilian city economical organization from the plural perspective on the economy which was inspired by the polanyian theory; b) verifying how the city human development index (CHDI) appears in cities where polanyian features are strong, expressed through the dimensions which form the multidimensional approach. The found results show that: a) according to the analyzed concepts, development in Brazilian cities are quite incipient; b) there is a direct and positive relation between PCDI and CHDI. The cities, where PCDI are better, also show a stronger CHDI, what reveals that economical plurality, somehow, influences social and economical features of the development progress which are wished and hoped.